The religious cultures of Dutch Jewry - Ḳaplan, Yosef; Mikhman, Dan (Brill's series in Jewish studies, 2017)
"In The Religious Cultures of Dutch Jewry an international group of scholars examines aspects of religious belief and practice of pre-emancipation Sephardim and Ashkenazim in Amsterdam, Curaçao and Surinam, ceremonial dimensions, artistic representations of religious life, and religious life after the Shoa. The origins of Dutch Jewry trace back to diverse locations and ancestries: Marranos from Spain and Portugal and Ashkenazi refugees from Germany, Poland and Lithuania. In the new setting and with the passing of time and developments in Dutch society at large, the religious life of Dutch Jews took on new forms. Dutch Jewish society was thus a microcosm of essential changes in Jewish history"--